Aktualisasi Jejak Kepemimpinan Ali bin Abi Thalib - Rahmat; Syukur, Syamzan; Muh. Idris (Rihlah : Jurnal Sejarah dan Kebudayaan, 2025)
This study is an effort to introduce the leadership of Ali bin Abi Talib through a     descriptive narrative and analytical disclosure, both the principles of leadership, the challenges in carrying out duties as a ruler, and the actualization of his leadership in a contemporary perspective. In order to elaborate on the leadership of this caliph, this study uses historical methods and approaches with an emphasis on modern historiography. The results of this study show All bin Abi Talib as the fourth caliph, the successor to the leadership of the Prophet Muhammad (peace be upon him), he is considered a figure who actualizes the temporal leadership of the Messenger of Allah based on the concepts of fatanah, siddiq, amanah, and tablik. This is evident in the principles of leadership that he implemented. In carrying out his duties as a leader, he faced very heavy challenges as a legacy from his predecessors. However, with the firmness of holding on to leadership principles in governance, he became a figure worthy of emulation in the contemporary era filled with turmoil.   Kajian ini adalah upaya memperkenalkan kepemimpinan Ali bin Abi Thalib melalui pengungkapan secara deskriptif naratif dan analitis, baik prinsip kepemimpinan, tantangan dalam menjalankan tugas sebagai penguasa maupun aktualisasi kepemimpinannya dalam perspektif kontemporer. Dalam rangka mengelaborasi kepemimpinan khalifah tersebut, kajian ini menggunakan metode dan pendekatan sejarah dengan penekanan historiografi modern. Dari hasil kajian ini menunjukkan Ali bin Abi Thalib sebagai khalifah keempat, pengganti kepemimpinan Nabi Muhammad saw. beliau dianggap sosok yang mengaktualisasikan kepemimpinan temporal Rasulullah dengan berdasar pada konsep fatanah, siddiq, amanah dan tablik. Hal ini terlihat pada prinsip-prinsip kepemimpinan yang dijalankannya. Dalam menjalankan tugas sebagai pemimpin beliau menghadapi tantangan yang amat berat sebagai warisan dari pendahulunya. Namun dengan keteguhan memegang prinsip kepemimpinan dalam menjalankan pemerintahan menjadikannya sosok yang patut ditiru pada era kontemporer yang penuh dengan pergolakan.